2017
DOI: 10.1111/gfs.12283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type of underlay film on fermentation profile, nutritional quality and estimated loss of organic matter in the outer layer of whole‐plant maize ensiled in large bunker silos

Abstract: Losses of organic matter in the outer layers of bunker silos covered with conventional polyethylene (PE) plastic can be substantial due to oxygen transmission through the plastic top‐covering film during the post‐ensiling storage period. The effect of two silo covering materials, oxygen barrier (OB) film (45 μm thickness) and clear PE film (50 μm thickness), as underlays to a white‐on‐black PE plastic top cover (120 μm thickness), was assessed in the outer layer of whole‐plant maize silage stored in three larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The chemical composition of the silage suggest that the corn was well preserved and is in agreement with studies similar to this (Robinson and Swanepoel, 2016;Wang et al, 2017). The DM content of WPCS was approximate to ideal DM (30-35%) for satisfactory silage .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The chemical composition of the silage suggest that the corn was well preserved and is in agreement with studies similar to this (Robinson and Swanepoel, 2016;Wang et al, 2017). The DM content of WPCS was approximate to ideal DM (30-35%) for satisfactory silage .…”
Section: Discussionsupporting
confidence: 87%
“…The diet had an average NEg of 1.18 Mcal/kg DM and TDN of 76.4%, the silage had NEg of 0.81 and TDN of 57.1%. Studies similar to this one also evaluated the effect of thin films with or without OB, both protected with double-sided PE film (Robinson and Swanepoel, 2016;Wang et al, 2017). The results showed only difference in the pH (OB = 3.73 vs. PE = 3.76) and lactic acid (OB = 5.85 vs. PE = 5.63% DM) (Wang et al, 2017) and without evidence of deterioration in silage, because the pH, fermentation products, microorganism count, temperature and nutrients, were similar (Robinson and Swanepoel, 2016).…”
Section: Animals and Experimental Dietsmentioning
confidence: 99%
“…Wang et al (39) compared plastic films composed exclusively of polyethylene to oxygen barrier films and found that the silage sealed with the polyethylene film lost 6.2 percentage units more organic matter compared to the impermeable film. Furthermore, according to the authors, the use of barrier film brought economic benefits in the order of US$ 0.74 for each ton of ensiled crop.…”
Section: Resultsmentioning
confidence: 99%